ANALISIS GERAKAN SEPARATISME DI PAPUA MENURUT UNDANG – UNDANG TERORISME - Delia Nadriah Awina Wirdatul Nadriah; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Separatism is an attempt to separate oneself from a country or state. Separatist efforts aim to achieve autonomy or separation to stand alone or to merge with other countries. Which has the aim of separating itself from a region or country, this is done to create an independent region or group and gain its own sovereignty as a new State. The main problems in this research are: Can the separatist movement in Papua qualify as terrorism? What are the obstacles to qualifying the separatist movement as Terrorism?The research method used in this thesis is using normative legal research methods, which is a process to find a rule of law, legal principles, and legal doctrines in order to answer the legal issues faced and by systematically reviewing norms and legal rules and data. from literature study.From the results of the study, there are two main problems that can be concluded. First, the activities of Separatism and Terrorism in the Criminal Code are two different things. Determination of Armed Criminal Groups in Papua or better known as KKB in Papua cannot have legal certainty because it is not in accordance with applicable positive law. Armed Criminal Groups in Papua cannot be prosecuted under Law Number 5 of 2018 because the KKB in Papua is a politically motivated separatist group. Second, law enforcement against these groups will be different from law enforcement in general regulated by the Criminal Procedure Code because the terrorism law is special and deviates from criminal law rules, this is due to the reason that they have political goals, so they cannot be charged under the law terrorism.Keywords : Separatism - Terrorism - Armed Criminal Group.